The policy planning system in Georgia: design and implementation challenges - Bacho Bitari Khuroshvili (Eastern Journal of European Studies)
Policy planning plays an essential role in public policy and administration, from academia to its practical application. This article examines the policy planning system in Georgia, focusing on its design and implementation. Two research questions guide this inquiry: (1) How is the policy planning system design formulated in Georgia, and how compatible is it with the OECD/Sigma standards? (2) How is the policy planning system implemented, and what explains the gaps between design and implementation? Methods such as in-depth interviews, document analyses, and expert surveys, along with the frameworks of comprehensive rationalism and incrementalism, illustrate the linkages between design and implementation. The research indicates that Georgia's policy planning system demonstrates partial compliance with SIGMA/OECD principles at 45.2%, showing legislative coherence but weaknesses in evidence-based policymaking and stakeholder inclusion. A significant gap exists between formal design and practical implementation, determined by limited administrative capacity, incremental policymaking, and weak political will.